G303 Taking ethical photos of children for medical and research purposes in low-resource settings: an exploratory qualitative study. (7th April 2014) - Devakumar, D; Brotherton, H; Halbert, J; Clarke, A; Prost, A; Hall, JA
Abstract : Background: Photographs of children are commonly taken in medical and research contexts. They can form a fundamental part of care, for example in documenting the progression of a disease, and are also commonly used to aid in teaching, advocacy and fund raising. With the increased availability of photographs through the internet, it is increasingly important to consider their potential for negative consequences and the nature of any consent obtained. Aims: We aimed to explore the issues around photography in low-resource settings, in particular concentrating on the challenges to gaining informed consent. Methods: Exploratory qualitative study using focus group discussions involving medical doctors and researchers who are currently working or have recently worked in low-resource settings with children. Results: Photographs are a valuable resource but photographers need to be mindful of how they are taken and used. All participants agreed that informed consent is needed when taking photographs but there were a number of problems in doing this, such as different concepts of consent, language and literacy barriers and the ability to understand the information. There was no consensus as to the form that the consent should take. Participants thought that while written consent was preferable, the mode of consent should depend on the situation. Conclusions: Photographs are a valuable but potentially harmful resource, thus informed consent is required but its form may vary by context. We suggest applying a hierarchy of dissemination to gauge how detailed the informed consent should be. Care should be taken not to cause harm, with the rights of the child being the paramount consideration.